Influence of seasonality on excursion demand: statistical approach - Hutsal , Liudmyla; Stoliar, Valentyna (Journal of Education, Health and Sport, 2023)
Studying the effect of seasonality on excursion demand is an important aspect in the management of the tourist business. Seasonal fluctuations in demand for excursion services reflect the changing preferences of tourists throughout the year and are determined by factors such as weather, cultural events, holiday periods and destination characteristics. The purpose of the article is to analyze seasonal trends in excursion demand based on statistical methods, which allows identifying patterns in consumer behavior and adapting the offers of tour operators to improve business efficiency. Based on the data, a regression and correlation analysis was performed to identify the key factors that affect fluctuations in the demand for excursions in different seasons of the year. The results of the study showed that the greatest demand falls on the summer period, especially for natural and cultural-historical objects. In the autumn-spring period, demand decreases, and in winter, interest in traveling to warm countries and Christmas markets increases. It was also found that factors such as average temperature and rainfall have a high influence on the choice of tourist destinations and the type of excursions. Based on the obtained results, recommendations were developed for tour operators regarding the differentiation of excursion offers in accordance with seasonal changes. Recommendations include flexible scheduling, adapting marketing strategies and activating advertising during peak demand periods. The use of such strategies will help increase the competitiveness of tour operators, optimize business processes and improve the quality of customer service.